Optimization of lipase-catalyzed nigella sativa L. oil-based ferulate esters production and their antioxidant activity - Azhari, Farihin (2019)
Nowadays, the generation of novel product from natural substance has received tremendous attention due to the health benefits. Nigella sativa L. seed, also recognized as black cumin is a medicinal plant that possesses miraculous power of healing due to the abilities to cure various ailments excluding death. However, it is oily and prone to oxidative degradation. Ethyl ferulate was added to provide an antioxidative shield against lipid oxidation. The ester exhibits special features such as non-toxic, outstanding moisturizing action and good solubility characteristics but most importantly the absence of oily texture. In addition, the ester may consist of valuable characteristics from both the Nigella sativa oil (NSO) and ethyl ferulate (EF). In this study, long chain ferulate esters (LCFEs) were produced by transesterification of NSO with EF in the presence of Rhizomucor miehei immobilized lipase (Lipozyme RM IM). The production conditions were optimized by rotatable central composite design (RCCD) from response surface methodology (RSM) attaining maximum esters conversion of 49.87% under lipase dosage of 67 mg, temperature of 56°C, substrate ratio (NSO: EF) of 4.4: 1 (w/w) and time of 4 hours. The attained conversion value was in agreement with the predicted value of 48.82%. The produced LCFEs were characterized by fourier transform-infrared (FT-IR) spectroscopy, gas chromatography-mass spectrometry (GC-MS) and thin layer chromatography (TLC). FT-IR spectrum of LCFEs showed two common bands of ester group: C=O and C-O strong bands at 1763-1653 cm-1 and 1115-1100 cm-1, respectively. Long chain of aliphatic ester component was also present indicated by an absorption band at the range of 1480-1365 cm-1 region. The GC-MS analysis of LCFEs revealed that remaining EF (32.41%) and decreased amount of fatty acids (50.64%) were identified in comparison with substrates EF and NSO, correspondingly which confirmed the production of LCFEs. The fatty acids found in LCFEs including oleic acid and essential fatty acid such as linoleic acid. TLC showed the presence of LCFEs at retention factor, Rf = 0.64 showing the lowest polarity compared to NSO (Rf = 0.52) and EF (Rf = 0.28). Moreover, the antioxidant activity of LCFEs was analyzed by three different methods: 2,2-Diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3- ethylbenzothiazoline-6-sulphonic acid) (ABTS) and β-carotene bleaching (BCB). The produced LCFEs exhibited outstanding antioxidant property due to their high percentage inhibition (83.37 ± 3.42-85.88 ± 0.12%) as well as low IC50 value (47.79 ± 3.04-114.33 ± 3.95 μg/mL). Thus, LCFEs are potential source of natural antioxidant and can be used as alternative ingredient in cosmeceutical product.